PEMANFAATAN UMBI ILES-ILES SEBAGAI BAHAN BAKU BIOETANOL UNTUK BAHAN BAKAR ALTERNATIF DI PEDESAAN - Kusmiyati Kusmiyati; Maryati Maryati; Farida Nurcahyani; Ichsanudin Febrianto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
Bioethanol has attracted considerable attention as alternative fuel during the past decades. The main problem to the commercialization of bioethanol is the cost of raw material. Use an inexpensive raw material such as starchy material (Iles-Iles or Amorphophallus muelleri B.) is an attractive lower the cost of bioethanol. In this work, bioethanol was produced from iles-iles starch using four steps processes: hydrolysis by using enzym α–amylase and enzym glucoamylase, fermentation using yeast Saccharomyces cereviceae, distillation and adsorption using CaO. The initial iles-iles starch concentration used in this experiment was 25% and 40% w/v (g starch/l solution). For both of starch concentrations were hydrolyzed by sequence liquefaction and saccharification. For liquefaction, this carried out at 95-97°C, pH 6, 1% enzym α–amylase for 45 minutes. For saccharification, this treatment was carried out for 24 hours at 58-60°C by the used of enzym glucoamylase solution in various concentration (1%; 1.5%; 2%; 2.5% v/v) at a constant pH (5), and the used of constant glucoamylase solution (2% v/v) at various pH (4; 4.5; 5; 5.5). After hydrolysis, enzymatic fermentation was carried out for 76 hours at 30°C by the used of various concentration of yeast Saccharomyces cereviceae (0.6%; 0.8%; 1%; 1.2% w/v) at constant pH (4) and by the used of various pH (4; 4.5; 5; 5.5) at constant yeast Saccharomyces cereviceae concentration (1% w/v). After fermentation, bioethanol (95%) was obtained by two steps distillation. After distillation, adsorption process using CaO was carried out to obtain the highest bioethanol purity (99%). Enzymatic hydrolysis yielded glucose, based on the result the increasing of enzym glucoamylase increase the glucose yield. The result showed the decreasing pH increase the glucose yield. The highest amount of glucose (3.1% w/v) was obtained under conditions : 25% (w/v) iles-iles starch concentration, 2% (v/v) enzym glucoamylase, pH 4, 24 hours. A higher sugar concentration and, consequently, a higher final bioethanol concentration can be obtained by increasing the iles-iles starch concentration. Hydrolyzed starch was fermented by Saccharomyces cereviceae and yielded 7.8% (g ethanol/Kg iles-iles). The result of the research indicated that to produce 1 liter bioethanol 99% needs 9,4 kg Iles-iles tubers.